Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Disiplin Kerja Pada Karyawan CV. Wil Outdoor Tasikmalaya - Endang Al Mubarok (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of Work Motivation on Work Discipline in Employees of CV. WILD OUTDOOR TASIKMALAYA, to determine the influence of the Work Environment on Work Discipline in Employees of CV. WILD OUTDOOR TASIKMALAYA and knowing the effect of Work Motivation and Work Environment on Work Discipline in Employees of CV. WILD OUTDOOR TASIKMALAYA. The samples in this study were employees of CV. WILD OUTDOOR TASIKMALAYA, totaling 63 people. This research was conducted by collecting data using a questionnaire data collection technique, then testing the data with multiple linear regression analysis. The results of this study indicate that there is no effect of work motivation on work discipline in employees of CV. WILD OUTDOOR TASIKMALAYA. There is an influence of the Work Environment on Work Discipline in CV Employees. WILD OUTDOOR TASIKMALAYA. There is an influence of Work Motivation and Work Environment on Work Discipline in Employees of CV. WILD OUTDOOR TASIKMALAYA.